2021
DOI: 10.1161/circgen.121.003421
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Plasminogen Activator Receptor: Genetic Variation and Cardiovascular Disease Risk in Black Adults

Abstract: Background: suPAR (Soluble urokinase plasminogen activator receptor) has emerged as an important biomarker of coagulation, inflammation, and cardiovascular disease (CVD) risk. The contribution of suPAR to CVD risk and its genetic influence in the Black population have not been evaluated. Methods: We measured suPAR in 3492 Blacks from the prospective, community-based JHS (Jackson Heart Study). Cross-sectional associations of suPAR with lifestyle and CVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The same caution should be extended to findings generated using other high throughput affinity proteomics technologies vulnerable to non-specific protein binding, such as aptamer-based 77 , where missense single nucleotide polymorphisms can affect binding in a manner where a genetic difference drive associations, rather than protein levels (Supplementary information Fig. S 1f ) 78 , 79 . Studies comparing different affinity proteomics technologies have found correlations of proteins assayed with two or more platforms to range from highly concordant (Spearman´s ⍴ = 0.95) to inversely correlated ( ⍴ = −0.48) 78 , highlighting further the need for orthogonal validation of any potential biomarker identified.…”
Section: Discussionmentioning
confidence: 99%
“…The same caution should be extended to findings generated using other high throughput affinity proteomics technologies vulnerable to non-specific protein binding, such as aptamer-based 77 , where missense single nucleotide polymorphisms can affect binding in a manner where a genetic difference drive associations, rather than protein levels (Supplementary information Fig. S 1f ) 78 , 79 . Studies comparing different affinity proteomics technologies have found correlations of proteins assayed with two or more platforms to range from highly concordant (Spearman´s ⍴ = 0.95) to inversely correlated ( ⍴ = −0.48) 78 , highlighting further the need for orthogonal validation of any potential biomarker identified.…”
Section: Discussionmentioning
confidence: 99%
“…From a technological perspective, our study demonstrates the need for orthogonal verification of any potential biomarker identified using antibody-based proteomics screening [34, 35]. The same caution should be extended to findings generated using other high throughput affinity proteomics technologies vulnerable to non-specific protein binding, such as aptamer-based [74], where missense single nucleotide polymorphisms can affect binding in a manner where a genetic difference drive associations, rather than protein levels (Figure S1 F) [75, 76]. Studies comparing different affinity proteomics technologies have found correlations of proteins assayed with two or more platforms to range from highly concordant (r = 0.95) to inversely correlated (r = −0.48) [75], highlighting further the need for orthogonal validation of any potential biomarker identified.…”
Section: Discussionmentioning
confidence: 99%
“…Our GWAS analysis encompasses over 24,000 individuals in whom suPAR levels were measured using the suPARnostic (ViroGates) immunoassay used in the seminal studies on suPAR, kidney disease, and CVD outcomes ( 14 , 18 , 28 , 34 , 67 ). While our analysis included participants of mostly European ethnicity, a smaller GWAS in Black individuals also identified rs4760 as a determinant of suPAR levels measured using immunoassay ( 69 ). Finally, our experimental approach relies on the use of murine models of atherosclerosis, which cannot recapitulate all the features of the human disease, with major differences in lipoprotein metabolism and bile acid absorption ( 70 ).…”
Section: Discussionmentioning
confidence: 99%